Poverty Alleviation Strategy Policy Formulation in Toba Regency, North Sumatra Province - Marlan Hutahaean; Dimpos Manalu; Johnson Pasaribu (Iapa Proceedings Conference, 2020)
This paper aims to uncover the process of public policies formulation, specifically regarding poverty reduction strategies and social protection in Toba Regency, North Sumatra. The poverty reduction policy that is the focus of this research consists of three Regional Regulations (Perda), which were only issued in 2019, after the district was established (autonomy) since 1999, namely: Regional Regulation No. 2/2019 concerning the Implementation of Social Welfare, Regional Regulation No. 10/2019 concerning Protection and Fulfillment of the Rights of Persons with Disabilities, and Regional Regulation Number policy formulation11/2019 concerning the Implementation of Elderly Welfare. This qualitative research concludes that the process and formulation of poverty reduction policies in Toba Regency took place technocratically and elitist. First, the three Regional Regulations are considered as "derived regulations", the operationalization of a higher level of statutory regulation (in this case government laws and regulations), which are considered to have clear scope and conception. Secondly, the three regional regulations were drafted at the end of the government (executive) period and national legislative elections which have implications and the potential for ineffective implementation of policies and as well as minimal oversight of the legislative majority which is not elected in the next period. This factor caused suspicion towards the three Regional Regulations to be solely formulated for the pragmatic interests of the incumbent regents for the sake of popularity and electability in the next regional elections. Third, there is a lack of public participation because these three regional regulations have policy targets for socially, culturally and politically vulnerable and voiceless groups, as well as the lack of support from civil society organizations. Based on the findings above, the policy recommendation put forward is that public involvement in the process and formulation of this Perda is not merely administrative in nature, but an active sequence from the setting agenda to the formulation.